Chain Length Distribution of β‐amylase Treated Potato Starch and Its Effect on Properties of Starch Nanoparticles Obtained by Nanoprecipitation. (22nd July 2019) - Chang, Yanjiao; Yang, Jingde; Jiang, Longwei; Ren, Lili; Zhou, Jiang
Abstract : Potato starch solution is treated by using β‐amylase to shorten length of starch molecular chains. Chain length distribution of the β‐amylase treated potato starch is characterized by size exclusion chromatography and fluorophore‐assisted carbohydrate electrophoresis. Results show that the content of long chains with degree of polymerization >100 decreases from 22% to 6.5% after 360 min β‐amylolysis, and the amount of short chains considerably increased. Properties of starch nanoparticles (SNPs) fabricated via nanoprecipitation using the β‐amylase treated potato starch are characterized. It is found that the β‐amylolysis gave rise to smaller SNPs with narrower size distribution due to reduction of chain entanglements during precipitation. V‐type crystalline structure exists in the precipitated SNPs and the β‐amylase treatment does not influence crystalline structure and crystallinity of the obtained SNPs. Abstract : Potato starch solution is treated by β‐amylase hydrolysis. Chain length distribution of the starch is characterized by SEC and FACE. The β‐amylase treatment gives the starch nanoparticles obtained via alcohol precipitation smaller size and narrower size distribution.